2013
DOI: 10.4103/0973-029x.125200
|View full text |Cite
|
Sign up to set email alerts
|

VEGF and CD 34: A correlation between tumor angiogenesis and microvessel density-an immunohistochemical study

Abstract: Background:Angiogenesis is the formation of new vessels from preexisting ones which takes place by capillary sprouting. It is seen in healing, at sites of injury and collateral circulation in ischemia. It is also seen in tumors, as once the original blood supply of a tumor is exhausted it cannot grow without further blood supply. Also as the angiogenic capacity of a tumor increases, its microvasculature, that is, microvessel density (MVD) also increases. Based on this literary evidence we carried out an immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 16 publications
1
20
0
1
Order By: Relevance
“…Our results showed that CD24 expression was closely related to MVD, especially in liver metastasis tissues of human CRC patients. These datas suggested that CD24 possiblely promoted the CRC metastasis by regulating the expression of VEGF, which was responsible for tumor MVD [34]. We further confirmed that alerted CD24 expression could affect CRC cells migration, invasion and tubule formatting.…”
Section: Discussionsupporting
confidence: 72%
“…Our results showed that CD24 expression was closely related to MVD, especially in liver metastasis tissues of human CRC patients. These datas suggested that CD24 possiblely promoted the CRC metastasis by regulating the expression of VEGF, which was responsible for tumor MVD [34]. We further confirmed that alerted CD24 expression could affect CRC cells migration, invasion and tubule formatting.…”
Section: Discussionsupporting
confidence: 72%
“…These results suggest that RAGE may act as a potential regulatory factor of microvessel formation in endometrial cancer, although a similar phenomenon has previously been observed in renal cell carcinoma [ 6 ] and colorectal cancer [ 7 ]. Folkman (1971) first proposed the concept of angiogenesis-dependent tumour growth [ 17 ], as once the original blood supply is exhausted, the tumour cannot grow without further blood supply [ 18 , 19 ]. The evidence accumulated to date indicates a direct link between microvessel status and cancer development, and a growing body of data suggests that microvessel density is potentially involved in tumour recurrence, metastasis, and survival [ 9 , 10 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported that MVD acts as an independent prognostic factor and is also not associated with tumor grade. [ 53 ]…”
Section: Discussionmentioning
confidence: 99%